Readiness of M-Learning: a study of Politeknik Kota Bharu students / Kamilah Zainuddin, Amaal Fadhlini Mohamed and Noor Asmaa Hussein - Zainuddin, Kamilah; Mohamed, Amaal Fadhlini; Hussein, Noor Asmaa' (Universiti Teknologi MARA, 2022)
M-Learning has become a crucial component of electronic learning due to the quick development of mobile technologies. It has made learning possible at any time and anyplace with the usage of wireless internet and mobile equipment, hence it is seen as a potentially significant learning aid. However, learners' readiness should be taken into account before designing and putting into place a replacement learning system. Despite its obvious benefits, Malaysian polytechnics have done limited studies on M- Learning. This quantitative study investigates how prepared Malaysian polytechnic students are for M- Learning. Purposive sampling was used to pick 285 students from Politeknik Kota Bharu to administer a questionnaire for this reason. Three key preparedness areas namely equipment readiness, technological skill readiness, and psychological readiness were the focus of the questionnaire. The overaching conclusion is that the vast majority of students exhibited a high level of preparation for the use of M-Learning. The type of gadgets utilized during the M-Learning session strongly correlates negatively with the students' readiness. The results of this study can provide educators and curriculum designers with important information about how to promote M-Learning in their teaching and learning processes.